Knowledge of, and attitudes towards, adult vaccination among General Practitioners in Piedmont, Italy: results from a cross-sectional study - Pizzini, S.; Vicentini, M.; Fassone, R.; Fiasca, F.; Mattei, A.; Venier, V.; Venesia, R.; Morato, P. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. “Life-course immunization” is increasingly recognized as important. In Italy, adults are recommended to receive influenza; pneumococcal; tetanus toxoid, reduced diphtheria toxoid, acellular pertussis (Tdap); and herpes zoster (HZ) vaccines at various ages. Study design. Cross-sectional study.Methods. To study the knowledge and attitudes of Italian general practitioners (GPs) towards adult vaccination, we surveyed 335 GPs in Piedmont from December 2019 through March 2020; and compared the results by GPs’ age (≤50 vs >50 years). Results. The most common vaccination information source was the regional/local educational courses (72.8%), with older vs younger GPs more likely to attend (79.4% vs 64.4%; p=0.002). Approximately half felt that they needed further information on vaccine co-administration (55.5%), duration of protection (49.6%), and safety/tolerability (48.7%), with older vs younger GPs being more interested in safety/tolerability. Overall, most respondents (86.0%) felt that information for the patient would most engage them, and 68.1% planned to co-administer vaccines. Respondents felt most comfortable proposing influenza, but were also comfortable about pneumococcal/Tdap/HZ vaccination. However, younger vs older GPs were more comfortable about proposing Tdap and HZ. The most common ways to inform patients about influenza or pneumococcal/Tdap/HZ vaccination eligibility were personally during a visit (42.7% or 54.3%, respectively) or via an information poster (30.7% or 17.9%). Conclusions. The surveyed GPs had favorable attitudes towards adult vaccination and were interested in ongoing education.